Between friars and dignities. The dispute for the administrative relief at the real de San José Hospital of Valladolid (Morelia), 1694-1708 (Tzintzun, Revista de Estudios Históricos, 2021)
In 1694, by initiative of the 14th Bishop of the diocese of Michoacán, the basis to substitute the diocese administration of the Real de San José Hospital in Valladolid with a religious one, the Hospitaller Order of the Brothers of Saint John of God, was established. To support this initiative, the Crown issued a decree ordering the church in Michoacán to carry out such relief in the best way. Nevertheless, the traditional antagonism between the two clergies, the conviction of the Diocesans to have been the victims of a dispossession, and the intransigeant attitude of the Hospitaller brothers on that subject, contributed to a delay in the process and propitiated a controversial climate of confrontation that characterizedevery single moment of the difficult decade the relief lasted. The present work addresses this scarcely studied episode of the history of the Real de San José Hospital of Valladolid.
Keywords: Real de San José Hospital in Valladolid; church of Michoacán; Diocesan; ospitaller brothers; administrative relief